2017
DOI: 10.1080/19390211.2017.1404544
|View full text |Cite
|
Sign up to set email alerts
|

Seeds of Buchholzia coriacea in Diet Mitigate Ischemic Reperfusion–Induced Gastric Ulceration in Experimental Rats

Abstract: Buchholzia coriacea (B. coriacea) seeds, in folk medicine, have been documented to prevent gastric ulceration though the mechanism is not fully elucidated. To clarify this, the gastro-healing activities were investigated using graded incorporation of B. coriacea seeds in the diet. Male Wistar rats (150-200 g) were divided into 7 groups (n = 15): unulcerated untreated control, ulcerated untreated control, unulcerated B. coriacea low (10%), ulcerated B. coriacea low (10%), nulcerated B. coriacea high (25%), ulce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…The increase may be due to the decrease in the level of serum and hepatic antioxidant defences. The anti-lipid peroxidation activity exhibited by HEBCS in this study supports the recent report by Salami et al [54] on reduction in MDA levels after ingestion of diets supplemented with Seeds of Buchholzia coriacea.…”
Section: Hebcs (E) There Is a Mild Periportal Cellular Infiltration supporting
confidence: 92%
“…The increase may be due to the decrease in the level of serum and hepatic antioxidant defences. The anti-lipid peroxidation activity exhibited by HEBCS in this study supports the recent report by Salami et al [54] on reduction in MDA levels after ingestion of diets supplemented with Seeds of Buchholzia coriacea.…”
Section: Hebcs (E) There Is a Mild Periportal Cellular Infiltration supporting
confidence: 92%
“…Owonikoko et al [16] reported that Buchholzia coriacea seeds in diet hastened gastric ulcer curative rate in acetic acid induced gastric ulcer in rats. Similar report by Salami et al [17] on Buchholzia coriecea treatment and ischemia-reperfusion gastric ulcer reported better healing rate ascribed to its ability to suppress gastric acid secretion. More notably for this study is the anti-hyperglycemic and the anti-diabetic properties reported for this plant with dearth of knowledge on the role of the intestine in glucose uptake when treated with Buchholzia coriecea.…”
Section: Introductionsupporting
confidence: 84%
“…Free radicals and lipid peroxidation play a pivotal role in the pathogenesis of indomethacin-and ethanolinduced gastric ulcer (Sabiu et al, 2015;Sahoo et al, 2016;Sistani et al, 2019). Antioxidants mop up free radicals and inhibit lipid peroxidation thus, useful in the amelioration of gastric ulcer (Salami et al, 2018). The anti-ulcer activity of MFCS could be linked to its antioxidant potentials.…”
Section: Discussionmentioning
confidence: 99%